Aplikasi Sistem Informasi Akademik Berbasis Website (Studi Kasus : Sekolah Dasar Maitreyawira Batam) - Roni Zeki; Yonky Pernando; Martina Prativi (J-Com (Journal of Computer), 2022)
Abstract: Everything at Maitreyawira Elementary School in Batam is done manually, and the existing computer is only used to make reports. Every academic activity at Maitreyawira Elementary School Batam includes gathering information about students, teachers, and mentors as well as gathering information about the curriculum itself. You can access accurate and up-to-date information during data processing through a web-based information system. Seeing the current situation at Maitreyawira Batam Elementary School with a manual access system, it is necessary to develop an information system that can facilitate the process of accessing relevant data from the database. To make it easier, a design with UML was carried out, which will later be tested on the website of the academic information system at the Maitreyawira Elementary School Batam. It can help process academic data to produce valid information and can use the academic information system at the Maitreyawira Elementary School Batam to help teachers input value quickly and accurately. Keywords: Website; Academic Information System; UML; Elementary School  Abstrak: Sekolah Dasar Maitreyawira Batam dilakukan secara manual, dan komputer yang ada hanya digunakan untuk membuat laporan. Setiap kegiatan akademik di Sekolah Dasar Maitreyawira Batam meliputi pengumpulan informasi tentang siswa, guru, dan mentor serta mengumpulkan informasi tentang kurikulum itu sendiri. Untuk memperoleh informasi yang akurat dan up-to-date selama pengolahan data, Anda dapat mengaksesnya melalui sistem informasi berbasis web. Melihat situasi saat ini di Sekolah Dasar Maitreyawira Batam dengan sistem akses manual, maka perlu dikembangkan sebuah sistem informasi yang dapat mempermudah proses pengaksesan data yang relevan dari database. Untuk mempermudah maka dilakukan sebuah perancangan dengan UML yang nantinya akan diujikan kedalam website sistem informasi akademik di Sekolah Dasar Maitreyawira Batam dapat membantu mengolah data akademik untuk menghasilkan sebuah informasi yang valid dan dapat menggunakan sistem informasi akademik di Sekolah Dasar Maitreyawira Batam mampu membantu para guru untuk input nilai dengan cepat dan tepat. Kata kunci: Sistem informasi akademik; Website; UML; Sekolah Dasar